2014
DOI: 10.1089/cbr.2014.1706
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Enzyme Inhibition Improves the Targeting of [177Lu]DOTA-GRP(13–27) in GRPR-Positive Tumors in Mice

Abstract: Coadministration of PA significantly increased the percentage of intact radiopeptide in the mouse circulation. From biodistribution and ex vivo autoradiography studies, coadministration of both lysine and PA with [(177)Lu]DOTA-GRP(13-27) appeared to induce a clear improvement of tumor uptake as well as lower levels of renal radioactivity, causing a promising ninefold increase in tumor/kidney ratios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…In addition, radiolabeled-BnR-agonists/antagonists have been co-administered with neutral endopeptidase inhibitors, which are one of the major proteolytic enzymes for Bn related peptides[81], which has resulted in enhanced uptake in tumor xenografts.…”
Section: Imaging and Targeted-delivery Of Cytotoxic-agents To Neopmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, radiolabeled-BnR-agonists/antagonists have been co-administered with neutral endopeptidase inhibitors, which are one of the major proteolytic enzymes for Bn related peptides[81], which has resulted in enhanced uptake in tumor xenografts.…”
Section: Imaging and Targeted-delivery Of Cytotoxic-agents To Neopmentioning
confidence: 99%
“…A number of recent studies using various radiolabeled( 188 Re, 55/57 Co, 111 In, 64 Cu, 99M Tc, 68 Ga, 18 F) BnR-agonists(primarily-GRPR-agonists) show imaging[16•,73,74,100,121,145,146,147•,148155] or targeted-tumoral delivery of cytotoxic-radioisotopes( 177 Lu, 188 Re, 111 In, 64 Cu, 18 F)[16,74,77,100,147•,154] to prostate-cancer-cells both in vitro [16,73,74,81,121,145147•,149,152155] and in vivo to image prostate-cancer xenografts in nude-mice[16•,73,74,77,81,100,121,145,146,147•,148,149,151155]. In two comparative studies in vivo of xenografts of the prostate-cancer-cell-line[155,156], PC-3, in nude-mice, a 68 Ga-labeled-BnR-agonist or 18 F-labeled-Bn-antagonist(BAY 86-4367) showed greater tumor-uptake with lower background than a metabolic probe, which is increasingly used in prostate-cancer patients.…”
Section: Bn-peptides-bnr: Prostate-cancermentioning
confidence: 99%
See 2 more Smart Citations
“…In one study of 7 patients refractory to 90 Y/ 177 Lu-DOTATATE, all demonstrated enduring responses with favorable acute and midterm toxicity with 213 Bi-DOTATOC[104]. Other approaches being taken to increase the cytotoxicity of 90 Y-/ 177 Lu in PRRT include the use of combination therapies including using 90 Y-/ 177 Lu-DOTATATE together[105]; combined with PARP inhibitors to potentiate the accummulation of double-stranded DNA breaks and cytoxicity[106]; with peptide-degradation inhibitors such as phosphoramidon to increase tissue uptake[107, 108] or with chemotherapeutics to increase sensitivity such as temozolomide, or capecitabine and other anti-tumor agents such as everolimus[30, 109112]. …”
Section: Molecular Imaging Of Neuroendocrine Tumorsmentioning
confidence: 99%